Privilegios de Indias - Benedict XIV, Pope, 1675-1758.
Volume (177 leaves) containing an alphabetical extract of rights and privileges of Indians in Mexico.
Collection material in Spanish.
Keywords: Catholic Church -- Mexico; Indians of Mexico